New Polyketides With Anti-Inflammatory Activity From the Fungus Aspergillus rugulosa - Xu, Qianqian; Qiao, Yuben; Zhang, Zijun; Deng, Yanfang; Chen, Tianqi; Tao, Li; Xu, Qiaoxin; Liu, Junjun; Sun, Weiguang; Ye, Ying; Lu, Yuanyuan; Qi, Changxing; et al. (Frontiers in Pharmacology, 2021)
Two new polyketide compounds, asperulosins A and B (1–2), one new prenylated small molecule, asperulosin C (3), along with nine known compounds (4–12), were isolated and identified from a fungus Aspergillus rugulosa. Their structures were extensively elucidated via HRESIMS, 1D and 2D NMR analysis. The absolute configurations of new compounds were determined by the comparison of their electronic circular dichroism (ECD), calculated ECD spectra, and the detailed discussion with previous reports. Structurally, compounds 1 and 2 were belonging to the polyketide family and from different origins. Compound 2 constructed by five continuous quaternary carbon atoms, which occurred rarely in natural products. All of the isolates were evaluated for anti-inflammatory activity against the production of nitric oxide (NO) in LPS induced RAW264.7 cells. Among which, compounds 1 and 5 showed a significant inhibitory effect on NO production with IC50 values of 1.49±0.31 μM and 3.41±0.85 μM, respectively. Additionally, compounds 1 and 5 markedly increased the secretion of anti-inflammatory cytokine IL10, while suppressed the secretion of proinflammatory cytokines IL6, TNF-α, IFN-γ, MCP-1 and IL12. Besides, 1 and 5 inhibited the transcription level of pro-inflammatory macrophage markers IL6, IL1β, and TNF-α, while remarkably elevated the anti-inflammatory factor IL10 and M2 macrophage markers ARG1 and CD206. Moreover, 1 and 5 restrained the expression and nuclear translocation of NF-κB, as well as its downstream signaling COX-2 and iNOS. All these results suggest that 1 and 5 has potential as an anti-inflammatory agent, with better or comparable activities than positive control dexamethasone.